Aβ under stress: the effects of acidosis, Cu2+-binding, and oxidation on amyloid β-peptide dimers. Issue 56 (27th June 2018) - Liao, Qinghua; Owen, Michael C.; Bali, Sofia; Barz, Bogdan; Strodel, Birgit
Abstract : In light of the high affinity of Cu 2+ for Alzheimer's Aβ1–42 and its ability to subsequently catalyze the formation of radicals, we examine the effects of Cu 2+ binding, Aβ oxidation, and an acidic environment on the conformational dynamics of the smallest Aβ1–42 oligomer, the Aβ1–42 dimer. Abstract : In light of the high affinity of Cu 2+ for Alzheimer's Aβ1–42 and its ability to subsequently catalyze the formation of radicals, we examine the effects of Cu 2+ binding, Aβ oxidation, and an acidic environment on the conformational dynamics of the smallest Aβ1–42 oligomer, the Aβ1–42 dimer. Transition networks calculated from Hamiltonian replica exchange molecular dynamics (H-REMD) simulations reveal that the decreased pH considerably increased the β-sheet content, whereas Cu 2+ binding increased the exposed hydrophobic surface area, both of which can contribute to an increased oligomerization propensity and toxicity.